APLIKASI PASSWORD GENERATOR DENGAN METODE DICEWARE BERBASIS WEB MOBILE - ARIFUDIN, WAHYU; Lusiana, Veronica (Information Technology and Telematics, 2018)
Abstract- People often choose a password that is easy to remember, for example from the date of birth, the name of the parent and so on. Often these passwords are easy to guess. Besides, those passwords are also easy to penetrate using some password cracking techniques such as dictionary attacks or brute-force attacks. Making a password that is safe but easy to remember is not an easy thing. The longer and more complex a password, the safer the password is. There are several methods that can be used to create a secure password. Diceware password is a method that can be used to make passwords safe but easy to remember. System development method used in this research is waterfall which consists of the beginning of the system, system analysis, system design using UML, system implementation using PHP and MySQL.The final result of this research is the mobile web-based password generator application can be used to facilitate and help the general public in creating passwords that are easy to remember and safe with the diceware method which consists of password generator 1 key and password generator 3 key with a maximum of 8 random times where the password results diceware will show as pdf